1997
DOI: 10.1295/polymj.29.598
|View full text |Cite
|
Sign up to set email alerts
|

Orientational Ordering of a Dimer Liquid Crystal by High-Resolution Solid-State 13C NMR Spectroscopy

Abstract: ABSTRACT:The ordering of a dimer liquid crystal, IX,w-bis [(4,4'-cyanobiphenylyl)oxy]decane (CBA-10), was studied by variable-temperature high-resolution solid-state 13 C NMR. A large transitional change of the 13 C chemical shift was observed on going from the isotropic to the nematic phase due to uniaxial alignment of the molecule. The principal values of the 13 C chemical shift tensor have been determined by the Herzfeld-Berger method for CBA-10 itself. The molecular axis is assumed to lie parallel to the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…20 Shimizu et al also reported that the ordering of the mesogens and of the molecule itself to increase with a decrease in temperature in the nematic phase, whereas that of spacer remains almost constant. 21 It is thought that the difference in the n dependency of TN 1 and ASN1 results from an alteration of the ordering of mesogens in the nematic phase. This point will be clarified based on additional study on n dependence of TN 1 and ASN 1 for many dimeric liquid crystals which have various mesogens.…”
Section: Thermal Propertiesmentioning
confidence: 99%
“…20 Shimizu et al also reported that the ordering of the mesogens and of the molecule itself to increase with a decrease in temperature in the nematic phase, whereas that of spacer remains almost constant. 21 It is thought that the difference in the n dependency of TN 1 and ASN1 results from an alteration of the ordering of mesogens in the nematic phase. This point will be clarified based on additional study on n dependence of TN 1 and ASN 1 for many dimeric liquid crystals which have various mesogens.…”
Section: Thermal Propertiesmentioning
confidence: 99%
“…A homologous series of dimer, trimer, and polymer LCs having PM-type spacers have been studied carefully using various methods, such as 2 H-NMR (quadrupolar splittings) (Section 7.3.1), Faraday balance (magnetic susceptibility) [Sigaud et al, 1983], SQUID (magnetic susceptibility) [Esnault et al, 1988;Furuya et al, 1990Furuya et al, , 1991, and 13 C-NMR ( 13 C chemical shift tensor, 13 C-13 C dipolar couplings) [Shimizu et al, 1997[Shimizu et al, , 1998]. Studies on dimers were extended further to include the effect of the size and orientation of mesogenic units [Furuya et al, 1986], the effect due to the tilting angle at the junction joining the mesogenic unit with the spacer [Abe et al, 1995b], and the optical anisotropy of the partially ordered spacer and its contribution to the orientation-dependent attractive interactions [Furuya et al, 1995].…”
Section: Molar Mass Dependence Of Thermodynamic Quantities: Studies Omentioning
confidence: 99%
“…The oscillation representing the internal trans-gauche correlation of the bond rotation was found to be more pronounced for the spacer with n = even (Section 7.3.3). The molecular scheme described above has also been adopted successfully in an analysis of the observed 13 C chemical shift and the 13 C-13 C dipolar coupling data of the dimer and trimer LC compounds [Shimizu et al, 1997[Shimizu et al, , 1998]. …”
Section: Elucidation Of the Nematic Conformation Of Flexible Spacersmentioning
confidence: 99%
“…Since the degree of polymerization (DP) dependence of physical properties is expected to be most distinct in the oligomer region, a homologous series of dimer (also called a twin compound), trimer, and polymer LCs having α,ω-dialkoxyalkane spacers were carefully examined in our previous work. Efforts were made to elucidate the conformational ordering of the spacer 4 by using various methods such as 2 H NMR (quadrupolar splitting), SQUID (anisotropy of the magnetic susceptibility), , and 13 C NMR ( 13 C chemical shift tensor, 13 C− 13 C dipolar coupling). , Studies were further extended to include the effect of the size and orientation of mesogenic units, the effect due to the disorientation (tilting angle) at the junction jointing the mesogenic unit with the spacer, and the optical anisotropy of the partially ordered spacer and its contribution to the orientation-dependent attractive interactions . The main emphasis was placed on the thermodynamics involved in the formation of the LC state of the main-chain LC compounds .…”
Section: Introductionmentioning
confidence: 99%